Color controllable smart white lighting based on various device architectures of electrically driven quantum-dot light-emitting diodes. Issue 29 (14th July 2022) - Shin, Dong-Wook; Lee, Sanghyo; Choi, Hyung Woo; Bang, Sang Yun; Han, Soo Deok; Cho, Yul Jae; Fan, Xiang-Bing; Jo, Jeong-Wan; Ni, Limeng; Samarakoon, Chatura; Arbab, Adrees; Yang, Jiajie; et al.
Abstract : Device architectures of patterned-, stacked-, and mixed-type quantum-dot light-emitting diodes (QD-LEDs) for the next-generation smart white lighting have been analyzed and optimized by computational charge transport simulation and experiments. Abstract : A comprehensive study of the various device architectures of patterned-, stacked-, and mixed-type quantum-dot light-emitting diodes (QD-LEDs) for smart white lighting has been performed by way of computational simulation and experimental device fabrication. The layout of the patterned-type QD-LED has been optimized by a rigorous charge transport simulation and a numerical grid searching color optimization method. The patterned-type QD-LED devices are fabricated using a unique transfer printing technique to validate design concepts. The architectural dependency on the color of the stacked-type QD-LED has been computationally and experimentally explored by the charge transport simulation with the electric-field-dependent carrier hopping model and by fabricating the devices with a multi-step spin-coating process. The mixed-type QD-LED has also been experimentally analyzed by the QD volume mixing ratios in the mixture solution. These three types of patterned, stacked, and mixed QD-LED device architectures show potential for various applications of functionalized next-generation smart white lighting systems.